2022
DOI: 10.3389/fcell.2022.942225
|View full text |Cite
|
Sign up to set email alerts
|

Association of aging-related genes with prognosis and immune infiltration in pancreatic adenocarcinoma

Abstract: Pancreatic adenocarcinoma (PAAD) is one of the deadliest malignancies. Aging is described as the degeneration of physiological function, which is complexly correlated with cancer. It is significant to explore the influences of aging-related genes (ARGs) on PAAD. Based on The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) datasets, we used univariate Cox regression analysis and acquired eight differentially expressed ARGs with prognostic values. Two molecular subtypes were identified based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The study of aging-related prognostic models in cancer has attracted more and more attention. Xue et al (2022) identified a novel seven-ARG risk signature to predict prognoses of pancreatic adenocarcinoma. Compared with it, our prognosis model has higher precision.…”
Section: Discussionmentioning
confidence: 99%
“…The study of aging-related prognostic models in cancer has attracted more and more attention. Xue et al (2022) identified a novel seven-ARG risk signature to predict prognoses of pancreatic adenocarcinoma. Compared with it, our prognosis model has higher precision.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, a series of aging-related genes were associated with prognosis and responsiveness to immunotherapy [ 24 ]. Xue et al also developed an aging-related prognostic signature for pancreatic adenocarcinoma [ 25 ]. Another study also constructed a prognostic signature based on 9-aging related genes for acute myeloid leukemia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%